2017
DOI: 10.1002/jbm.a.36262
|View full text |Cite
|
Sign up to set email alerts
|

One pot synthesis of new poly(vinyl alcohol) blended natural polymer based magnetic hydrogel beads: Controlled natural anticancer alkaloid delivery system

Abstract: Facile one-pot synthesis has been demonstrated for new biocompatible and dual responsive magnetic iron oxide nanoparticles cross-linked poly(vinyl alcohol) (PVA) blended natural polymer chitosan (CS) based hydrogel beads (mCS-PVA) as a controlled natural anticancer alkaloid Luotonin A (LuA) delivery system. The prepared magnetic hydrogel beads were characterized using powder X-ray diffraction measurement, Fourier transform-infrared spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Releasing of nano RIF from the mCS‐PEG gel beads were found to be higher than same in the absence of the magnetic field. This indicated that the magnetic field as an external stimulus inducing the release of nano RIF from the magnetic gel beads . The mechanism involved as the applied magnetic field collapses the cross‐linking pattern of the CS‐PEG gel network via attracting the crosslinked MIONs toward the edges of sphere shaped gel beads (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Releasing of nano RIF from the mCS‐PEG gel beads were found to be higher than same in the absence of the magnetic field. This indicated that the magnetic field as an external stimulus inducing the release of nano RIF from the magnetic gel beads . The mechanism involved as the applied magnetic field collapses the cross‐linking pattern of the CS‐PEG gel network via attracting the crosslinked MIONs toward the edges of sphere shaped gel beads (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…This indicated that the magnetic field as an external stimulus inducing the release of nano RIF from the magnetic gel beads. 43 The mechanism involved as the applied magnetic field collapses the cross-linking pattern of the CS-PEG gel network via attracting the crosslinked MIONs toward the edges of sphere shaped gel beads (Scheme 4). As a result, the loaded nano drugs on polymer chains as well as on the surface of MIONs were released through diffusion.…”
Section: M1mentioning
confidence: 99%
“…However, any potential polysorbate 80 surfactant residue and the hydrogel’s pore structure are easy problems to solve . The selection of polysorbate 80 surfactant in the preparation process should be done to ensure sufficient pore formation and to allow for a standard structure …”
Section: Resultsmentioning
confidence: 99%
“…24 The selection of polysorbate 80 surfactant in the preparation process should be done to ensure sufficient pore formation and to allow for a standard structure. 25 Due to their good histocompatibility and low immunogenicity, hydrogels have inherent advantages in medical research and application. The introduction of magnetic particle materials makes the hydrogels responsive to magnetic fields, which is in line with current medical science and the increasing demand for medical materials to be intelligent and controllable.…”
Section: In Vitro Degradationmentioning
confidence: 99%
“…[4][5][6] Nanostructured materials functionalized with organic or inorganic coatings were developed as alternatives for the clinical studies of cancer therapy through attacking solid tumors. [6][7][8][9][10][11] The use of magnetic nanoparticles was introduced as a novel technical approach for cancer diagnosis and treatment with optimum anti-cancer effects. 12 Furthermore, L-lysine, L-arginine and 3-aminopropyltriethoxysilane (APTES) were employed to coat negatively charged nanoparticles; this increased the chances of nanoparticles binding to the anionic cell membrane.…”
Section: Introductionmentioning
confidence: 99%